2021
DOI: 10.3389/fphar.2021.731483
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Improves Cognitive and Neuronal Function in 3-NP Rat Model of Huntington’s Disease

Abstract: Huntington’s disease (HD) is an autosomal dominant inherited neurodegenerative disease characterized by progressive motor, psychiatric, and cognitive abnormalities. The antidiabetic drug liraglutide possesses a neuroprotective potential against several neurodegenerative disorders; however, its role in Huntington’s disease (HD) and the possible mechanisms/trajectories remain elusive, which is the aim of this work. Liraglutide (200 μg/kg, s.c) was administered to rats intoxicated with 3-nitropropionic acid (3-NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Neuroinflammation is involved in a number of neurodegenerative illnesses, including PD, AD, and HD, where activation of astrocytes and microglia is evident. 62 Herein, our results revealed that repaglinide mitigated the robust microgliosis and astrocytic activation and subsequent neuronal inflammation as reflected in the substantial reduction in Iba1 and GFAP immunostaining as well as IL-6 and IL-1β levels, suggesting its anti-inflammatory properties. The excessively activated microglia and astrocytes coexisted with rotenone exposure were previously echoed in a PD rat model, along with its exacerbating effect on neuronal apoptosis and neuroinflammation.…”
Section: Acs Chemical Neuroscience Pubsacsorg/chemneuromentioning
confidence: 58%
“…Neuroinflammation is involved in a number of neurodegenerative illnesses, including PD, AD, and HD, where activation of astrocytes and microglia is evident. 62 Herein, our results revealed that repaglinide mitigated the robust microgliosis and astrocytic activation and subsequent neuronal inflammation as reflected in the substantial reduction in Iba1 and GFAP immunostaining as well as IL-6 and IL-1β levels, suggesting its anti-inflammatory properties. The excessively activated microglia and astrocytes coexisted with rotenone exposure were previously echoed in a PD rat model, along with its exacerbating effect on neuronal apoptosis and neuroinflammation.…”
Section: Acs Chemical Neuroscience Pubsacsorg/chemneuromentioning
confidence: 58%
“…This was in agreement with the study of Wang et al, who postulated that old diabetic rats displayed reduced spatial learning and short- and long-term memory [ 52 ]. Treatment with either liraglutide [ 47 ] or pramlintide [ 9 ] resulted in more or less normal results of spontaneous T maze as well as NOR test in both treated groups as compared to the diabetic group.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies discussed how PRAM might improve cognitive function considering the importance of the native role of amylin in the regulation of oxidative processes and neuronal function [ 39 ]. Anti-apoptotic properties and oxidative stress reduction of PRAM and LIRA therapy seem to contribute to neurological recovery [ 11 , 28 , 47 , 62 ]. A similar finding was observed by Patrick et al, who stated that amylin treatment revealed restored lost mitochondrial membrane potential [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…AD affects approximately 55 million people worldwide and is more frequent between 75 and 84 years old (Alzheimer's Association, 2021; WHO, 2022), whereas PD is the second most prevalent neurodegenerative disease affecting 2-3% of the population over 65 years old (Poewe et al, 2017). Moreover, HD, which affects 5 to 7 individuals per 100,000 inhabitants aged between 30 and 50 years (Bruzelius et al, 2019), is also an important neuropathology (Shawki et al, 2021). In a simplified way, AD, PD, and HD mainly impair neuronal structures and functions in part due to the aberrant accumulation of certain aggregated proteins: amyloid-beta (Aβ) in AD, α-synuclein in PD (Kulenkampff et al, 2021;Shawki et al, 2021), and huntingtin (HTT) in…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HD, which affects 5 to 7 individuals per 100,000 inhabitants aged between 30 and 50 years (Bruzelius et al, 2019), is also an important neuropathology (Shawki et al, 2021). In a simplified way, AD, PD, and HD mainly impair neuronal structures and functions in part due to the aberrant accumulation of certain aggregated proteins: amyloid-beta (Aβ) in AD, α-synuclein in PD (Kulenkampff et al, 2021;Shawki et al, 2021), and huntingtin (HTT) in…”
Section: Introductionmentioning
confidence: 99%